Peranan Bimbingan Dan Konseling Dalam Pendidikan Islam - Suparwan Suparwan (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2015)
By nature, human beings are created by God as a religious with keksistensiannya and live together. Human beings are born as a berunsurkan monopluralis body and spirit accompanied with reason and conscience and the passions are given the freedom to wills. However, it requires a responsibility that must be endured, and it can not be run with the maximum and may be difficult to be accomplished without the guidance of the parties concerned.In this case counseling has a very important role, in which counseling is an advisory activity with or in the form of suggestions and suggestions in the form of communicative conversation between the counselor and the client by using psychological methods on the basis of systematic knowledge about human personality in efforts to improve mental health clients.The bottom line is the main element in the implementation of the counselor to do is to inculcate the basic teachings of Islam with said Al-Qur'an and Hadith, for which there are values that are very good if actually applied in daily life, so that all men can accept and understand about life and how to deal with it especially Muslims, and in this case counseling pempunyai very important role to achieve.